Sir HC Dinshaw Building - Ghosh, Ayan (2023)
Facade of Sir HC Dinshaw Building at 16 Horniman Circle. The building was constructed in 1924 on the location of the Bank of Bombay (now the premise of State Bank of India), which was the first building erected on the Circle. The building is one of many establishments owned by the Parsi community in and around the Horniman Circle.